Versatile vacuum-powered artificial muscles through replaceable external reinforcements - Mendoza, Mijaíl Jaén; Cancán, Sergio; Surichaqui, Steve; Centeno, Esteban; Vilchez, Ricardo; Bertoldi, Katia; Vela, Emir A. (Frontiers in Robotics and AI, 2024)
Soft pneumatic actuators are a well-known actuation scheme that has offered safe, lightweight, and conformable robotic machines. However, each actuator is strongly associated to a default output motion in existing schemes due to their fixed shape and design. In this study, we propose the use of replaceable reinforcements opening the possibility to modify the shape of soft actuators. Our actuator consists of a versatile vacuum-powered artificial muscle (VPAM) with external reinforcements that can be replaced manually. Tuning the output motion is achieved through beams that work as replaceable external reinforcements, enabling a single artificial muscle to perform different motions. Our results show that our VPAM is reusable and versatile producing a variety and sophisticated output motions such as twisting, bending, shearing and rotary as well as their combinations if needed. This key feature specially benefits unpredicted workspaces that require a soft actuator that can be adjusted and be reused in other tasks. Our scheme has the potential to offer new strategies for locomotion in machines for underwater or terrestrial operation, and wearable devices with different modes of operation.